2020
DOI: 10.1101/2020.03.22.20040915
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using early data to estimate the actual infection fatality ratio from COVID-19 in France

Abstract: Background. The number of screening tests carried out in France and the methodology used to target the patients tested do not allow for a direct computation of the actual number of cases and the infection fatality ratio (IFR). The main objective of this work is to estimate the actual number of people infected with COVID-19 and to deduce the IFR during the observation window in France.Methods. We develop a 'mechanistic-statistical' approach coupling a SIR epidemiological model describing the unobserved epidemio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 18 publications
3
93
0
1
Order By: Relevance
“…Under-reporting or over-estimation of COVID-19 deaths According to Roques et al (2020), the Infection Fatality Ratio (IFR) for COVID-19 is 0.5% (95%-CI: 0.3; 0.8). Figure S2 shows that using this IFR over-estimate compared to the death currently reported by Santé Publique France.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under-reporting or over-estimation of COVID-19 deaths According to Roques et al (2020), the Infection Fatality Ratio (IFR) for COVID-19 is 0.5% (95%-CI: 0.3; 0.8). Figure S2 shows that using this IFR over-estimate compared to the death currently reported by Santé Publique France.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that ICU (t, ξ i ) = 0.25 × H(t, ξ i ) which is consistent with the prevalence of ICU cases among hospitalized cases at the French national level. Based on the estimation of the Infection Fatality Ratio (IFR) from Roques et al (2020), we get a rough estimation of D(t, ξ i ) as 0.5% of R(t, ξ i ). Roques et al (2020) conclude that COVID-19 fatalities are under-reported, and using their IFR estimate we adequately fit the trend of the observed COVID-19 deaths but with an offset due to this assumed higher IFR, see Appendix A1.…”
Section: Compartments Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study [12], we applied this framework to the data corresponding to the beginning of the epidemic in France (from February 29 to March 17), with a SIR model. Our primary objective was to assess the infection fatality ratio (IFR), defined as the number of deaths divided by the number of infected cases.…”
Section: Introductionmentioning
confidence: 99%
“…There is a wide spectrum of estimates of µ in the literature, see e.g. [3], [4], [6], based on complete tests conducted on small closed populations exposed to COVID-19, but there appears to be a consensus that the actual range should be between 0.1% and 1.0%. The difficulty lies of course in the fact that the IFR is based not only on the observed cases, but also on undiagnosed and asymptomatic cases.…”
mentioning
confidence: 99%